2010
DOI: 10.3109/02713680903453494
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of DA-6034 on Ocular Inflammation via Suppression of MMP-9 and Inflammatory Cytokines and Activation of the MAPK Signaling Pathway in an Experimental Dry Eye Model

Abstract: These results suggest that DA-6034 has the therapeutic effect in rabbit lacrimal gland inflammation model of dry eye and might be a potential treatment option for acute dry eye syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…66 We have also shown that Gelatinase B (MMP-9) was the most abundant gelatinolytic enzyme present in tears, elevated approximately twofold in eyes with pterygia versus the contralateral control eyes. 70 This may be a contributing factor 77 to the ocular surface inflammation and dry eye syndrome seen in pterygium patients 78 -perhaps presenting another therapeutic opportunity in treatment with topical cyclosporine. 79 Another potential mode of action of cyclosporine is by the inhibition of the tachykinin NK1 receptors 80 that we have localized to infiltrating fibroblasts, mononuclear cells and the epithelia of pterygia.…”
Section: Peripheral Light Focusing and Pterygium Pathogenesismentioning
confidence: 97%
“…66 We have also shown that Gelatinase B (MMP-9) was the most abundant gelatinolytic enzyme present in tears, elevated approximately twofold in eyes with pterygia versus the contralateral control eyes. 70 This may be a contributing factor 77 to the ocular surface inflammation and dry eye syndrome seen in pterygium patients 78 -perhaps presenting another therapeutic opportunity in treatment with topical cyclosporine. 79 Another potential mode of action of cyclosporine is by the inhibition of the tachykinin NK1 receptors 80 that we have localized to infiltrating fibroblasts, mononuclear cells and the epithelia of pterygia.…”
Section: Peripheral Light Focusing and Pterygium Pathogenesismentioning
confidence: 97%
“…Other possible new treatments include DA-6034 which showed therapeutic efficacy by restoring tear function and inhibiting inflammatory response in a rabbit lacrimal gland inflammation model of dry eye (Seo et al, 2010), and phosphodiesterase 4 (PDE4) inhibitors which have the potential to control ocular surface inflammation by increasing cAMP levels (Govek et al, 2010). Recently, the demonstration of corneal lymphangiogenesis in DED, associated with significant increases in expression of pro-lymphangiogenic factors VEGF-C, VEGF-D, and VEGFR-3, and the detection of increased level of VEGF in tears of patients with dry eye (Enríquez-de-Salamanca et al, 2010), have opened the potential for new therapeutic approaches.…”
Section: Strategies For Controlling Ocular Surface Inflammationmentioning
confidence: 99%
“…Importantly, a family of extracellular endoproteinases called ‘matrix metalloproteinases’ (MMPs) has been implicated in HSK [6]. The two most widely studied members of this family, MMP-2 and MMP-9 (gelatinase A and gelatinase B), are known as the primary extracellular matrix remodeling enzymes that participate in pathologic conditions of the cornea such as infection, dry eye and neovascularization [7,8,9]. However, few studies have addressed the potential link/interaction between TNF-α and MMPs in HSK.…”
Section: Introductionmentioning
confidence: 99%